Pemanfaatan Berkelanjutan Gas Suar Bertekanan dan Bertemperatur Rendah Untuk Mengurangi Emisi Gas Rumah Kaca - Rosyani; Nazarudin; Ardi (Jurnal Pembangunan Berkelanjutan, 2020)
Gas Flaring serves to protect gas processing equipment from excess pressure. Usually also used in precarious conditions, the flare system will burn the entire process gas. In oil exploration, refineries and chemical plants, the main purpose of using flares is as a safety equipment to protect vessels or pipes from over-pressure. Flaring gas usually comes from the upstream oil and gas business (Upstream Industry) and from downstream business (Downstream Industry). Basically, flare installation is a safety system for a gas produced from the processing and production process by burning the gas. Aside from being a safeguard, flare gas combustion aims to minimize environmental pollution because if the gas is discharged into the air without being burned first, it certainly has a negative impact on the surrounding environment, because it can trigger fire, explosion and poisoning. But with the burning of this gas, it also has another negative impact that is increasing gas emissions which can have an impact on the greenhouse effect. Therefore, being burned or not burned will both have a negative impact, the best solution is to be utilized, so that it is not only beneficial to the user, but also friendly to the surrounding environment. Not all flaring gases can be utilized, there are several conditions where flaring gases are difficult to use, especially flaring gases which have low pressure will be difficult to distribute, as well as low temperature gases which trigger freezing so that it is difficult to be channeled. Then a unit of equipment called a mini gas compressor is needed to increase the existing pressure, and a double pipe heat exchanger to increase the existing temperature, so that the flare gas can be flowed and utilized. Low pressure gas which ranges below 50 psig will flow to the mini gas compressor, resulting in an increase in pressure to almost 200 psig. With this pressure, the gas can be channeled to the Gas Collection Station (GCS) and subsequently used as gas injection to increase production or flow to PLN as a selling gas. At low temperatures the gas will freeze when it flows into the Gas Collection Station, so that the freezing does not occur, the gas will pass the double pipe heat exchanger which has been flowed with hot temperatures, so that the gas can melt, and gas can continue to flow from the gas well to the Collecting Station Gas for further utilization